(3TQM JUQja GHf GdMGLHs - (3YKeGf Hf YeQ Hf CHj HcQ Hf jhfS GdeGdcj GdcQOj GdCSfGFj GdeUQj , CHh YeQh LeGd GdOjf GHf GdMGLH , J (B646 (3g` s
(3BNQgG (B:s
(3ai GdOdGdI Ydi GdHGA ZGdHkG Je s
(3GdTGajI ai GdJUQja dGHf GdMGLH GfXQ cTa GdXfhf L(B2 (3U` (B1020s
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B211 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B265s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdUQas